Clinico-radiological and ophthalmic spectrum of patients with Idiopathic Intracranial Hypertension and its correlation with severity of headache and visual impairment: a single center observational study - Abhishek Kumar; Ashok Kumar; Neetu Sinha; Abhay Ranjan (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background Idiopathic Intracranial Hypertension (IIH) is a syndrome of raised intracranial pressure (ICP) of unknown etiology. If untreated, it can result in progressive and irreversible vision loss. This prospective observational study was carried out to describe the epidemiological risk factors and clinical profile including spectrum of ophthalmological and radiological findings in Indian population. Fifty-one consecutive newly diagnosed patients presenting between Jan 2020 and Dec 2021 were included in this study. Clinical findings, demographic details, cerebrospinal Fluid opening pressure, Retinal Nerve Fiber Layer thickness, Perimetry, and Magnetic Resonance Imaging findings were noted in a pre-designed study proforma. The collected data were put to statistical analysis to draw inference regarding the clinical, demographic, and radiological profile of IIH. Results Fifty-one patients were enrolled in the study out of which 46 were females and 5 were males. The mean ± SD age at presentation was 30.4 (± 9.5) years. The mean ± SD Body Mass Index (BMI) was 26.66 ± 3.48 kg/m2. Headache was seen in 100% cases. Papilledema was seen in 98% cases. Enlarged blind spot was seen in 66.7% cases. Transverse Sinus Stenosis (TSS) was seen in 76.5% cases. The mean ± SD CSF opening pressure was 30.04 ± 4.176 cm H2O (range 25 cm–42 cm H2O). Cerebrospinal Fluid Opening Pressure (CSFOP) was significantly associated with severity of the headache and visual impairment with p < 0.001 and p = 0.005, respectively. Dilated optic nerve sheath was significantly associated with severity of visual impairment. Conclusion Most common epidemiological risk factors associated with IIH in Indian population are female sex of childbearing age and obesity. Headache is the most common symptom, while papilledema is the most common clinical sign. CSF opening pressure is significantly associated with the severity of the headache and visual impairment.